Sleep inadequacy and the relationship with mucosal immunity and upper respiratory symptoms in elite swimmers: A longitudinal study leading into the Commonwealth Games - Lauren H. Baker; Terun Desai; Jonathan Sinclair; Amy V. Wells (PLoS ONE, 2026)
Objectives To monitor sleep patterns of elite swimmers and explore sleep as a potential risk factor for upper respiratory symptoms (URS) alongside salivary Immunoglobulin A (IgA) in elite swimmers, over an 8-month competitive season. Design Secondary analysis of an 8-month longitudinal study in elite international swimmers leading into either the Commonwealth Games 2018 or Swim Cup Eindhoven. Methods Fourteen elite swimmers (age ± SD = 19.9 ± 0.8 years, height = 178.9 ± 6.3 cm, and mass = 75.0 ± 7.7 kg) were recruited. Self-reported sleep quality, URS data and salivary IgA was obtained weekly on a standardised day. Quantitative sleep parameters were measured using wrist-worn actigraphy four times for two-week bouts; during low, moderate, high training loads and once leading into competition. Results Swimmers waking fatigued was positively associated with frequency (p < 0.001) and severity (p < 0.001) of URS, plus negatively associated with salivary IgA (p = 0.035). Perception of meeting 7–9 hour national sleep recommendations was positively associated with URS frequency (p < 0.001) and severity (p = 0.001). Average sleep duration was 06:30 hrs: mins and reduced significantly during high training loads (p = 0.001) and early morning training (5:00 hrs: mins, p = 0.001). Average sleep efficiency was 81% over the 8-month period. Conclusions Perceived fatigue on waking was significantly associated with both frequency and severity of URS, and inversely associated with mucosal immunity (salivary IgA), providing novel insight into the relationship between sleep, fatigue and illness in this cohort. Although causality cannot be established, the high prevalence of inadequate sleep shown in elite swimmers highlights the importance of individual sleep monitoring to support recovery and inform strategies aimed at illness prevention.